ANALISIS TREN PERTUMBUHAN REKSA DANA SYARIAH DI INDONESIA PADA ERA EKONOMI - Rhisma Dillawati; Nurbaeti Nurbaeti; Dini Selasi (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Using a literature review and qualitative descriptive approach, this study investigates the growth trends of Islamic mutual funds in Indonesia during the period 2020–2025. The results show that the net asset value (NAV), number of investors, and a stronger digital ecosystem indicate positive growth for Islamic mutual funds. The digital transformation carried out by fintech platforms is crucial for improving access, transparency, and investment literacy. However, industry optimization is still hampered by issues such as a lack of knowledge about Islamic finance and a lack of product variety. Overall, as an inclusive and sustainable investment instrument, Islamic mutual funds have many opportunities.